Pengaruh Capital Adequacy Ratio Dan Non Performing Loan Terhadap Rerurn On Assets Pada PT. Bank Bumi Arta Tbk. - Hajar Andriana, Nurul; Afriyani; Abbas, Muliati; Sadariah (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2025)
The purpose of this study is to determine the Effect of Capital Adequacy Ratio and Non-Performing Loan on Return On Asset in PT. Bank Bumi Arta, Tbk. The types of data used in this study are qualitative and quantitative. The data source used in this study is secondary data. The analysis methods used are descriptive analysis and multiple linear regression, determination coefficient (R2), correlation coefficient (r), t-test, and F test. The results of this study show the regression equation Y = 0.975 + 0.006X1 - 0.236X2, determination coefficient, (R2) = 99.5% and correlation coefficient (R) = 0.997. Simultaneously, the Capital Adequacy Ratio and Non-Performing Loan have a significant effect on Return On Asset. Partially Capital Adequacy Ratio has a positive and significant effect on the Return On Asset, Non-Performing Loans has a negative and significant effect on Return On Aset at PT. Bank Bumi Arta Tbk . Thus Hypothesis 1, hypothesis 2, and hypothesis 3 are rejected.